Perancangan Kebijakan Sistem Ketenagalistrikan Kawasan Institut Teknologi Kalimantan - Aprillia, Happy; djafar, alfian; Filiana, Firilia (SPECTA Journal of Technology, 2023)
The Kalimantan Institute of Technology (ITK) already has 17 study programs and 3002 active students until 2021 and is projected to have 20 study programs by 2025. However, geographical location of ITK affect ITK facilities readiness that later supporting tridharma activities to be carried out perfectly. The Mechanical, Electrical and Plumbing System (MEP) at the ITK Campus needs to be designed with a sustainable design in order to accommodate the needs of electricity, sound, air conditioning, clean water, and dirty water on the ITK Campus until 2025. This study aims to design a sustainable MEP design for distribution of electricity especially in lightning protection in order to meet the characteristics of safe, reliable and appropriate design. The stages involved include 8 (eight) processes, namely: 1) data collection and design of the existing MEP, 2) projecting the growth of the academic community and equipment needs until 2025, 3) reviewing the existing MEP system as the existing protection system, 4) calculation of the suitability of the existing MEP system based on projected needs, SNI and SPLN, 5) planning for improvement of existing systems and plans for developing MEP systems, 6) making working drawings of the MEP system, 7) drafting Bill of Quantity MEP, and 8) MEP budgeting. This research is expected to produce output in the form of MEP planning drawings that are recommendation of detailed engineering design which are documented in strategic policies through the rector's regulation. This research is aimed to be used as a reference for MEP design for ITK development in the future development.